Evaluation of information available on the web to patients undergoing splenectomy in Japan - Masahiko Kita (PEC Innovation)
Objective: To evaluate the medical information available on the Web in Japanese to patients undergoing splenectomy. Methods: Japanese websites on splenectomy were identified by conducting a search on two Internet search engines. Scales were used to score readability, quality, understandability, and actionability. Correlation coefficients for the scale scores were calculated. Results: 31 Japanese websites were included in the analysis. “The increased lifetime risk of infection post-splenectomy” and “the requirement to carry a patient card or another form of identification indicating post-splenectomy” was mentioned in 90.3 % (28/31) and 3.2 % (1/31) of websites, respectively. The mean (±standard deviation) grade on the Japanese Readability was 9.8 (±0.9). The actionability of 22 websites was less than 30 %. Positive correlations were found between readability and DISCERN scores (γ = 0.37; 95 % confidence interval [CI], 0.01 to 0.64, p < 0.05) and between content score and actionability (γ = 0.49; 95 %CI, 0.07 to 0.69, p < 0.05). Conclusions: Japanese information on websites available to patients undergoing splenectomy was insufficient. The dissemination of information on specific infection prevention measures is needed but must be available at an appropriate readability level. Innovation: Creating patient education materials using content score items may promote splenectomy patients coping infection prevention behaviors in Japan.